NATIONAL SCHOOL FOR GRAPE AND WINE PRODUCTION OF MENDOZA STRENGTHENS LINKS WITH THE REGIONAL ENTREPRENEURS (1919-1925) - Rodríguez Vázquez, Florencia (2013)
This article deals with the institutional reconstruction of the National School for Grape and Wine Production (Escuela Nacional de Vitivinicultura) since the date of its reopening, in 1920. This was a turning point as regards the school’s organization and education policies, and it meant a greater connection with wineries owners and the response to a growing request for economic diversification, made apparent during the 1914 wine industry crisis, in Argentina. With this contribution we intend to continue the studies on the School through time and to enlighten its relation with the productive context.